2023
DOI: 10.1002/dmrr.3603
|View full text |Cite
|
Sign up to set email alerts
|

Statin use in patients with type 2 diabetes has lower risk of hip fractures: A Taiwan national population‐based study

Abstract: Aims Type 2 diabetes mellitus (T2DM) frequently co‐exists with osteoporosis and dyslipidemia. Statins have been commonly used in the treatment of dyslipidemia. Recent studies have indicated a therapeutic role of statins in decreasing the risk of osteoporosis and fractures, but conflicting results have been reported. This study investigated the association between statin use and hip fracture (HFx) risk among T2DM patients. Materials and Methods A retrospective Taiwan population‐based propensity‐matched cohort s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
(97 reference statements)
0
2
0
Order By: Relevance
“…31 . Another recently published study has shown that treatment with statins in adults with type 2 diabetes mellitus was associated with a lower risk of hip fractures demonstrating a dose-response relationship 32 .…”
Section: Accepted Manuscriptmentioning
confidence: 94%
“…31 . Another recently published study has shown that treatment with statins in adults with type 2 diabetes mellitus was associated with a lower risk of hip fractures demonstrating a dose-response relationship 32 .…”
Section: Accepted Manuscriptmentioning
confidence: 94%
“…We read with great interest the article 'Statin use in patients with type 2 diabetes has lower risk of hip fractures: A Taiwan national population-based study' by Tien-Ching Lee et al 1 They described that statin use was a significant and independent protective factor of hip fractures with an adjusted HR of 0.69. In addition, they noted a significant dose-response relationship between statin use and hip fracture risk.…”
Section: Editorsmentioning
confidence: 99%